Clinical integration of germline findings from a tumor testing precision medicine program - Maria Carolina Sanabria-Salas; Nina C. Anggala; Brittany Gillies; Kirsten M. Farncombe; Renee Hofstedter; Larissa Peck; Helia Purnaghshband; Laura Redondo; Emily Thain; Wei Xu; Peter Sabatini; Philippe L. Bedard; et al. (BMC Cancer)
Abstract Background Integrating germline genetic testing (GGT) recommendations from tumor testing into hereditary cancer clinics and precision oncology trials presents challenges that require multidisciplinary expertise and infrastructure. While there have been advancements in standardizing molecular tumor boards, the implementation of tumor profiling for germline-focused assessments has only recently gained momentum. However, this progress remains inconsistent across institutions, largely owing to a lack of systematic approaches for managing these findings. This study outlines the development of a clinical pathway for identifying potential germline variants from an institutional tumor-sequencing research program at Princess Margaret Cancer Centre. Methods Between August 2022 and August 2023, a clinical pathway led by a germline Molecular Tumor Board (gMTB) was established to review tumor genetic variants (TGVs) flagged as potential germline findings in patients with advanced cancer via a multigene panel. Eligibility for hereditary cancer syndrome investigation (‘germline criteria’) followed Cancer Care Ontario’s Hereditary Cancer Testing Criteria and clinical judgment. Germline-focused analysis of TGVs followed the European Society of Medical Oncology guidelines and similar published criteria (‘tumor-only criteria’). Results Of 243 tumor profiles, 83 (34.2%) had at least one TGV flagged by the genetic laboratory as potentially germline and were therefore referred to the gMTB for further review. Among these 83 cases, 47 (56.6%) met ‘germline criteria’ for GGT, regardless of the TGV assessment. A total of 127 TGVs were assessed in these 83 cases, of which 44 (34.6%) were considered germline relevant. Tier I TGVs, interpreted as pathogenic/likely pathogenic (P/LP) and found in most- or standard-actionable genes with high germline conversion rates (GCRs) in any context, were more likely to be considered germline relevant (p-value < 0.05). One confirmed germline variant was identified in nine patients meeting solely ‘tumor-only criteria’. Overall, 27/44 germline relevant TGVs underwent germline testing. We found a germline P/LP variant in 9 cases of the entire cohort, with a GCR of 33% (9/27). Conclusions Incorporating genetic counselors into gMTBs enhanced the integration of research findings into clinical care and improved the detection of disease-causing variants in patients outside traditional testing criteria.